2012
DOI: 10.1177/070674371205700202
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy: Theory and Practice

Abstract: Mindfulness-based cognitive therapy (MBCT) incorporates elements of cognitive-behavioural therapy with mindfulness-based stress reduction into an 8-session group program. Initially conceived as an intervention for relapse prevention in people with recurrent depression, it has since been applied to various psychiatric conditions. Our paper aims to briefly describe MBCT and its putative mechanisms of action, and to review the current findings about the use of MBCT in people with mood and anxiety disorders. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 51 publications
2
109
0
8
Order By: Relevance
“…Mindfulness may be an obvious choice of treatment for people with anxiety [38,39], given its focus on acceptance and living in the present moment [40]. A recent review of 19 studies using a mindfulnessbased treatment approach for various anxiety disorders found large effect sizes for improvements on both anxiety and depression, and a moderate effect on quality of life [41].…”
Section: Mindfulness To Treat Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness may be an obvious choice of treatment for people with anxiety [38,39], given its focus on acceptance and living in the present moment [40]. A recent review of 19 studies using a mindfulnessbased treatment approach for various anxiety disorders found large effect sizes for improvements on both anxiety and depression, and a moderate effect on quality of life [41].…”
Section: Mindfulness To Treat Anxietymentioning
confidence: 99%
“…In addition, mindfulness techniques, including meditation, have been used to increase acceptance and living in the present moment [40], which has resulted in reduced stress and anxiety among children [51], adolescents [52][53][54] and adults [38,43,46,55]. This study sought to explore the potential relationship between mindful meditation and both the symptoms of anxiety and asthma.…”
Section: Rationale For the Use Of Mindfulness For Asthma And Anxietymentioning
confidence: 99%
“…Sesje składają się z ćwiczeń medytacyjnych nakierowanych na rozwinięcie u uczestników uważności, połączonych z technikami poznawczo-behawioralnymi. Zgodnie z definicją twórców metody: "Mindfulness to rodzaj uważności, który powstaje przez celowe kierowanie uwagi na obecny moment oraz obserwowanie bez oceny zdarzeń takimi, jakie są" [7].…”
Section: Przebieg I Działanie Terapiiunclassified
“…W stanie bycia umysł przyjmuje rzeczywistość taką, jaka jest, bez oceny i próby zmiany. Jest jasne, że stan celowości jest przydatny i pomocny w rozwiązywaniu problemów życia codziennego, ale stosowanie go do wielu aspektów przeżycia wewnętrznego może prowadzić do chronicznego poczucia braku satysfakcji [7].…”
Section: Przebieg I Działanie Terapiiunclassified
“…Dr Walter E B Sipe and Dr Stuart J Eisendrath 10 have provided us with a clinically relevant and accessible introduction for the use of MBCT in people with mood and anxiety disorders. They note that MBCT, first described by Segal et al, 4 was initially conceived as an intervention to prevent relapse in patients with remitted major depression.…”
mentioning
confidence: 99%